Benzo[a]pyrene induces NLRP1 expression and promotes prolonged inflammasome signaling - Kohno, Risa; Nagata, Yuka; Ishihara, Tomohiro; Amma, Chisato; Inomata, Yayoi; Seto, Takafumi; Suzuki, Ryo (Frontiers in Immunology, 2023)
Benzo[a]pyrene (BaP), a polycyclic aromatic hydrocarbon in the air, triggers pulmonary inflammation. This study focused on BaP-induced inflammation in the alveolar epithelium. A549 cells were stimulated with BaP for four days. BaP treatment markedly increased NLRP1 expression but slightly decreased NLRP3. Furthermore, aryl hydrocarbon receptor (AhR) knockdown displayed no increase in BaP-induced NLRP1 expression. Similar results were also observed by blocking reactive oxygen species (ROS), which is mediated through AhR, suggesting that the AhR-ROS axis operates in BaP-induced NLRP1 expression. p53 involvement in ROS-mediated NLRP1 induction has also been implied. When we confirmed inflammasome activation in cells treated with BaP for four days, while BaP transiently activated NLRP3, it predominantly activated the NLRP1 inflammasome. These findings have led to the conclusion that BaP could be a potential ligand for the NLRP1 inflammasome persistently observed in the lung epithelium. Our study may provide additional evidence for the sustained pulmonary inflammation caused by environmental air pollution.